Jurnal Pengujian Kinerja Load Balancing Web Server menggunakan Nginx Riverse Proxy Berbasis OS Centos 7 - Muhamad Rafli (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The increasing number of visitor requests to the server results in the web server being down and experiencing slowness on the website if it is used in an amount that is considered to be in the millions, it will experience overload. One of the causes of the server being down is due to the inability to serve excessive requests, one way to improve and stabilize the performance of the web server is because there are very many service request accesses, then using the nginx load balancing system is a solution to overcome the occurrence of server downs. The nginx load balancing server can be tasked with distributing workloads to many servers, taking into account the capacity of each existing server. Nginx is supported by 3 algorithm methods (Round Robin, Least Connection, IP Hash) that can be used in nginx load balancing. The design of the nginx load balancing system in this study uses 2 laptops, the Windows operating system is assigned as a clinet with IP 192.168.1.22, Windows operating system as user IP 192.168.1.24, LVS (Linux Virtual Server) IP 192.168.88.251 server, Mikrotik router IP 192.168.88.1, in this test using supporting software, namely Jmeter, SNMP (Simple Network Management Protocol), PuTTY, Xampp, Laragon, Nginx. In this research, testing is carried out with the number of users 20,000, 30,000, 40,000 with 1 new request every 0.1 second through the jmeter and snmp applications. With the implementation of nginx load balancing, it can stabilize and maintain the balance of the web server and based on the results of research that has been tested the best algorithm method is round robin because it has significant stability and response time speed of 36ms and throughtput of 223.3/sec, the results of round robin bandwidth download are 467.2 k average upload 218.5k and maximum download 4039.8k maximum upload 2344.8k.